2010
DOI: 10.1002/ijc.25269
|View full text |Cite
|
Sign up to set email alerts
|

miR‐34c is downregulated in prostate cancer and exerts tumor suppressive functions

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that post-transcriptionally regulate gene expression. There have been several reports of miRNA deregulation in prostate cancer (PCa) and the biological evidence for an involvement of miRNAs in prostate tumorigenesis is increasing. In this study, we show that miR-34c is downregulated in PCa (p 5 0.0005) by performing qRT-PCR on 49 TURPs from PCa patients compared to 25 from patients with benign prostatic hyperplasia. The miR-34c expression was found to inversely corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 39 publications
13
113
1
1
Order By: Relevance
“…The tissues are described in the work by Hagman et al 11 and in Table 1. Cohort 2 consists of 71 FFPE samples (52 primary prostate cancers and 19 nonmalignant adjacent prostate) from radical prostatectomy (RP) obtained at Erasmus Medical Centre, Rotterdam, The Netherlands (Table 1).…”
Section: Patient Cohortsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tissues are described in the work by Hagman et al 11 and in Table 1. Cohort 2 consists of 71 FFPE samples (52 primary prostate cancers and 19 nonmalignant adjacent prostate) from radical prostatectomy (RP) obtained at Erasmus Medical Centre, Rotterdam, The Netherlands (Table 1).…”
Section: Patient Cohortsmentioning
confidence: 99%
“…In Cohort 1 small RNAs were extracted according to a modified protocol of mirVana TM miRNA Isolation Kit (Ambion, Austin, TX) as described in Hagman et al 11 In Cohort 2 deparaffinization and proteinase K treatment was done using High Pure RNA Paraffin Kit (Roche, Basel, Switzerland) according to the instructions of the supplier. Samples were mixed with 1 ml RNABee reagent (Campro Scientific, GmbH, Berlin, Germany) and total RNA was isolated according to the manufacturer's protocol.…”
Section: Rna Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, more than 50 miRNAs are abnormally expressed, leading to alteration in the expression and activity of their targets in PCa, such as miR-21, miR-320, miR-29b and miR34c (Ribas et al, 2009;Hagman et al, 2010;Hsieh et al, 2012;Ru et al, 2012 all prostate carcinoma samples compared with the BPH samples (Porkka et al, 2007;Watahiki et al, 2011). Several studies showed that the potential functions of miR-497 in human breast cancer (Li et al, 2011;Shen et al, 2012), neuroblastoma (Yadav et al, 2011), cervical cancer (Zheng et al, 2012), gastric cancer (Zhu et al, 2012) and colorectal cancer (Guo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…the tumour (82). restoration reduced levels of e2f3, a gene involved in cell cycle regulation at the g1/S checkpoint and was responsible for catalysing proliferation in prostate cell lines.…”
Section: P53 Mutation and The Role Of Mir-34 In Cancermentioning
confidence: 99%